PENATAAN LANSKAP BAHASA DALAM UPAYA PENINGKATAN POTENSI DESA WISATA DI DESA TOYOMARTO, KECAMATAN SINGOSARI, KABUPATEN MALANG - Ardhian, Dany; Fauzi, Nanang Bustanul; Setiawan, Romy; Warsiman, Warsiman; Abadi, Machrus (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Tourist spots in Toyomarto Village, Singosari District, Malang Regency need to be introduced to tourists. One tourism promotion strategy can be implemented by providing directional signage and information boards for these tourist locations. The signage and information boards are designed with high artistic quality and highlight the local characteristics and unique features of the tourist spots. This community service initiative is carried out with three objectives: (1) to document tourist spots, including archaeological sites, natural attractions, and traditional craft villages, as part of landscape planning efforts to integrate information; (2) to design directional signage and informational texts with artistic flair and local characteristics of the tourist spots; (3) to create and install these directional and informational signs in strategic locations within the tourist spot areas. The installation of these directional signs and information boards is expected to support tourism promotion efforts in Toyomarto Village, Singosari District, Malang Regency. This community service activity was carried out in collaboration with the Malang Regency Tourism Office, the Malang Regency Micro, Small, and Medium Enterprises Office, the Toyomarto Village Government, the Tourism Working Group, and micro-industry stakeholders. The results of the community service initiative indicate that there are seven key locations required for Phase I, specifically in the Pentungan Sari Tourism Area. These signs are focused on the following spots: gate (1 signboard), hall (2 signboards), swimming pool (2 signboards), toilet (1 signboard), café (1 signboard), and therapeutic fish pond (1 signboard).